PACEM: a new concept for high avalanche-ion blocking - Veloso, J. F. C. A. (2007)
We present the Photon-Assisted Cascaded Electron Multiplier (PACEM) as a potential alternative for ion back-flow suppression in gaseous cascade electron multipliers. Using a Micro Hole and Strip Plate-Gas Electron Multiplier (MHSP-GEM) configuration, the number of ions flowing back to the scintillation region is about 1.5 ions per primary electron at an optical gain of 6.5 and a drift field of 0.1 kV/cm, and about 10 ions per primary electron at an optical gain of 10 and a drift field of 0.5 kV/cm. These allow reaching ion back-flow values close to 10-4 and 10-5 at typical operation conditions of TPCs and GPMs, respectively.